Meningoencephalomyelitis of Unknown Origin in Cats: A Case Series Describing Clinical and Pathological Findings - Nessler, Jasmin; Wohlsein, Peter; Junginger, Johannes; Hansmann, Florian; Erath, Johannes; Söbbeler, Franz; Dziallas, Peter; Tipold, Andrea (Frontiers in Veterinary Science, 2020)
Meningoencephalomyelitis of unknown origin (MUO) is an umbrella term describing inflammatory changes of the central nervous system (CNS) with suspected non-infectious etiology. Diagnosis of MUO mostly remains presumed in a clinical setting. Histopathological and immunohistochemical examination of CNS tissue represent additional tools for detection of inflammation and the exclusion of specific infectious agents. While MUO are well described in canine patients, only little is known about MUO in cats. Previous reports of feline MUO involves either clinical findings or histopathological examination but not both. The present case series is the first report describing both clinical and histopathological findings of feline MUO: Four cats (age: 1.7 to 17.8 years) showed acute to chronic progressive neurological signs of encephalopathy or myelopathy. Three cats had extraneural signs (hyperthermia, weight loss, hyporexia, leukocytosis). Magnetic resonance imaging (MRI) showed multifocal intraparenchymal lesions in forebrain, brainstem or spinal cord with homogenous contrast enhancement. Cerebrospinal fluid (CSF) examination was normal or displayed albuminocytologic dissociation. Histopathology revealed a multifocal, lympho-histiocytic meningoencephalitis in three cases and a lympho-histiocytic myelitis in one case. Immunohistochemistry for feline parvovirus, feline coronavirus, feline herpesvirus, tick borne encephalitis virus, Borna disease virus, morbillivirus, rabies virus, suid herpesvirus-1, and Toxoplasma gondii were negative in all cases. Summary: This case series is the first one reporting both clinical and histopathological findings in cats with MUO. Feline MUO incorporates heterogeneous subtypes of sterile CNS inflammation.